The Impact of the Arabic Linguistic Principles on Guiding the Scientific Interpretation of the Qur'an - Meghaoui, Nedjoua (LANGUAGE ART, 2025)
Scientific miracles (I‘jaz ‘Ilmi’) represent one of the most recent fields of Qur'anic studies, focusing on uncovering the scientific and cosmic facts in the Qur'anic verses. Consequently, those engaging in this field must adhere to the standards and rules of the Arabic language, including morphology, grammar, semantics, and rhetoric, since it serves as the vessel for the words of Allah Almighty. Any deviation from these linguistic principles will inevitably lead to interpretive distortions, steering away from the correct and sound understanding of the meanings, rulings, and legal objectives conveyed in the Qur'an. As a result, the departure of some exegetes from these linguistic frameworks has led specific approaches to scientific interpretation into dangerous pitfalls, prompting many modern scholars to argue that the Qur'an does not contain aspects of scientific miracles. Moreover, others affirm their existence, provided that the necessary linguistic rules and guidelines are strictly observed.